Effect of Self-healing Training on Death Anxiety and Sleep Quality of Older Women Living in Nursing Homes - Laleh Jangi Jahantigh; Zohreh Latifi; Mohammad Soltanizadeh (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Aging is one of the important stages of human development. Death anxiety and sleep quality are among the most common mental health issues in the elderly which can be improved by proper intervention. This study aims to assess the effect of self-healing training on sleep quality and death anxiety of older women living in nursing homes. Methods & Materials This is a quasi-experimental study with a pretest/posttest/follow-up phase. The study population consists of all older women aged 60-70 years living in a nursing home in Isfahan, Iran in 2020. Of these, 40 were selected using a convenience sampling method and based on the inclusion and exclusion criteria, and were randomly assigned into two groups of intervention (n=20) and control (n=20). They were assessed by the Collett-Lester Fear of Death Scale and Pittsburgh Sleep Quality Index before, immediately after, and 45 days after the intervention. The intervention group received a 12-session self-healing intervention while the control group was placed in a waiting list without receiving any intervention. The results were analyzed by multivariate analysis of covariance in SPSS software, version 24. Results The self-healing training significantly improved the components of death anxiety (fear of own death, fear of the process of own dying, fear of the death of others, and fear of the process of others dying) and some of sleep quality components (subjective sleep quality, sleep latency, sleep disturbances, and use of sleeping medication) (P<0.05). These effects significantly remained constant in the follow-up phase in the components of fear of own death, subjective sleep quality, sleep latency, sleep disturbances and use of sleeping medication (P<0.05). No significant difference was found in other variables between the post-test and follow-up phases (P> 0.05). Conclusion The self-healing training can reduce perceived death anxiety and improve sleep quality of older women living in nursing homes. It can be used as an effective educational method for improving the lifestyle and mental health of older women living in nursing homes.